Pemetaan Parameter Oseanografi Kawasan Budidaya Rumput Laut di Perairan Kadia Liya Kabupaten Wakatobi - Alim Setiawan; Ihsan; Edyar Simon (AquaMarine (Jurnal FPIK UNIDAYAN ), 2021)
Kadia Liya is one of the seaweed-producing areas in Wakatobi Regency, Southeast Sulawesi Province. Seaweed farming activities in this area continue to grow. The development of aquaculture activities continues to grow because it is influenced by fairly good water conditions. Remote sensing mapping technology is the best alternative for monitoring the condition of oceanographic parameters on a regional scale. This study aims to map oceanographic parameters including salinity, dissolved oxygen, and acidity in the Kadia Liya seaweed cultivation area, Wakatobi Regency, sampling has been carried out at 20 station points spread across the cultivation area. The satellite imagery used is the Sentinel-2A satellite imagery. The method used in data processing is the interpolation method used, namely Inverse Distance Weighting (IDW) using the ArcGIS 10.8 application. The results of observations of water conditions include salinity with a range between 30.3 - 37.1 per mile (‰), dissolved oxygen (DO) which is 4.7 mg / l - 9.5 mg / l, and acidity (pH) which is 6.0 - 8.5. In general, the condition of oceanographic parameters such as salinity, dissolved oxygen, and acidity at the research site is still relatively suitable for seaweed cultivation activities.